On the Question of the Reception of French Parnassians by Kyiv Neoclassicists - Snizhynska, Maryna (Slavia Centralis, 2022)
The article describes the reception of the French Parnassians’ works by Kyiv Neoclassicists. This study is carried out with the comparative method. The main object of the work is the texts of Ukrainian authors which contain allusions to the works of their French predecessors of the XIX century, as well as the translations of Parnassians’ poetry made by Kyiv Neoclassicists. The article defines the common characteristics of these literary movements, such as attention to form, appeal to antique images and plots, and the shift away from Romanticism. The features of Neoclassicism have been identified, which distinguish it significantly from Parnassism due to the different cultural and political situation and time distance. The role is also analysed of French Parnassism in the formation and development of Kyiv Neoclassicism.